1970
DOI: 10.1136/gut.11.10.881
|View full text |Cite
|
Sign up to set email alerts
|

The selective nerve stain leucomethylene blue as an intraoperative aid to achieving complete vagotomy

Abstract: SUMMARYThe recently reported vagal nerve stain leucomethylene blue was assessed in 20 patients as an intraoperative aid to attaining complete vagotomy. Of 101 stained specimens removed at surgery, only 30 (30%) contained nerve tissue. Four of 17 postoperative insulin tests were positive by Hollander's criteria. The dye technique was found to be an unreliable method of ensuring complete vagotomy at the time of surgery.Due to the high incidence of incomplete vagotomy (Davies, 1956;Ross and Kay, 1964;Johnston, Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Lee reported that 80 per cent of the coloured removed twigs contained nerve tissue. Lee's study was confirmed by H0j and Wolf in 1972 (2) in an experimental study with rabbit vagal nerve twigs, but other authors (3,4) found that only 30 per cent of coloured specimens contained nerves. A controlled study published by Jensen et al in 1971 (5) found no difference in the postoperative reduction in fasting and basal acid output between a control group and a group of patients in which the LMB technique had been used.…”
supporting
confidence: 65%
“…Lee reported that 80 per cent of the coloured removed twigs contained nerve tissue. Lee's study was confirmed by H0j and Wolf in 1972 (2) in an experimental study with rabbit vagal nerve twigs, but other authors (3,4) found that only 30 per cent of coloured specimens contained nerves. A controlled study published by Jensen et al in 1971 (5) found no difference in the postoperative reduction in fasting and basal acid output between a control group and a group of patients in which the LMB technique had been used.…”
supporting
confidence: 65%
“…However, it selectively stains certain subpopulations of neurons in the brain, e.g. cerebellar Purkinje cells, where it binds to their dendritic spines (Müller, 1992) or polymorphic nerve cells in the hippocampal cornu ammonis, after supra-vital (intracardiac injection in deeply anesthetized animals) administration (Müller, 1998) and has been employed routinely for the staining of neuronal structures in clinical and histochemical studies (Frimer et al, 1970; Kristiansen, 1989; Müller, 1990; 1998; Seif et al, 2004). At the ultrastructural level, it was shown that MB appears as electron-dense precipitates staining the cytoplasm and chromatin homogeneously.…”
Section: Methylene Blue and Neurohistologymentioning
confidence: 99%
“…Lee (1969) introduced a method of applying a solution of leucomethylene blue to the outer aspect of the lower oesophagus at operation and alleged that the dye selectively stained nerve tissues, thus facilitating recognition of vagal strands during vagotomy. But others have not been impressed by its reliability or usefulness (Cox and Cooke, 1970;Frimer et al, 1970). Grassi (1971) designed a test which attempts to assess the completeness of vagotomy during the operation by determining the acidity of the mucosal surface before and after the nerve section by means of a pH probe.…”
Section: Assessment Of Different Operationsmentioning
confidence: 99%